IMPLEMENTASI KEBIJAKAN PELAYANAN TERPADU SATU PINTU PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI KALIMANTAN BARAT - Apriadi Apriadi (JPASDEV : Journal of Public Administration and Sociology of Development, 2021)
This research entitled "Implementation of One Stop Services Policy at the Regional Office of the Ministry of Religious Affairs, West Kalimantan Province". This research aims to examine and analyze the implementation process of the policy of One Stop Services (PTSP) at the Regional Office of the Ministry of Religious Affairs, West Kalimantan Province. PTSP Regional Office of the Ministry of Religion of West Kalimantan Province is an implementation from the Regulation of the Minister of Religious Affairs Number 65 of 2016 concerning Integrated Services at the Ministry of Religious Affairs. PTSP Regional Office of the Ministry of Religious Affairs of West Kalimantan Province have a purpose to improve the quality and public services to the society. However, in reality the PTSP in the Regional Office of the Ministry of Religious Affairs of West Kalimantan Province is not accordance with Regulation of the Minister of Religious Affairs Number 65 of 2016, so the author tries to analyze the implementation process of PTSP using the theory from Charles O. Jones. According to Jones, the implementation process consists of three stages, consisting of organization, interpretation, and application. The author examined PTSP Regional Office of the Ministry of Religious Affairs of West Kalimantan Province using descriptive research with a qualitative approach. The recommendation from  this research is that the Regional Office of the Ministry of Religious Affairs of West Kalimantan Province must follow the technical guidelines for integrated services that have been established by Ministry of Religious Affairs. Key words: (PTSP), implementation, service, organizing, interpretation, and application.